2024
DOI: 10.1002/eqe.4102
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of soil‐type index for shear wave velocity‐based liquefaction assessment

Nurhan Ecemis,
Mehmet Murat Monkul,
Murat Orucu

Abstract: The current simplified liquefaction assessment method based on the shear‐wave velocity, Vs has uncertainties about how the fine contents change the Vs‐based liquefaction resistance. According to the simplified method, for a given Vs, the cyclic resistance ratio (CRR) increases with an increase in fine contents. However, field investigations recently revealed that for various silty sands, the correlation between CRR and Vs is soil‐type index dependent and not specific for all sand‐silt mixtures with the same fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…silty sand has greater liquefaction resistance than the clean sand at a given V s1 > 170 m/s), whereas the opposite trend was observed for V s1 < 170 m/s (i.e. silty sand has smaller liquefaction resistance than the clean sand at a given V s1 < 170 m/s) (Ecemis et al 2024).…”
Section: Importance Of the "Crossing Effect" And Its Implications For...mentioning
confidence: 87%
See 1 more Smart Citation
“…silty sand has greater liquefaction resistance than the clean sand at a given V s1 > 170 m/s), whereas the opposite trend was observed for V s1 < 170 m/s (i.e. silty sand has smaller liquefaction resistance than the clean sand at a given V s1 < 170 m/s) (Ecemis et al 2024).…”
Section: Importance Of the "Crossing Effect" And Its Implications For...mentioning
confidence: 87%
“…In fact, a very recent study of the first author, involving Seismic Cone Penetration Tests (SCPT) on Silica sand-silt mixtures deposited in a rigid aluminum box, also revealed that Cyclic Resistance Ratio (CRR 7.5 ) vs. normalized shear wave velocity (V s1 ) curves could also show a trend similar to the "crossing effect" introduced in this paper. In that study, CRR 7.5 − V s1 curves for the sand-silt mixtures having different soil type indices (I c ) were shown to cross each other at around V s1 = 170 m/s (Ecemis et al 2024). Liquefaction resistance of silty sand with 10% FC becomes greater than that of the silty sand with 5% FC More specifically, for V s1 > 170 m/s, liquefaction resistance of the tested sand-silt mixtures was shown to increase with increasing I c (i.e.…”
Section: Importance Of the "Crossing Effect" And Its Implications For...mentioning
confidence: 89%